2022
DOI: 10.32604/cmc.2022.018270
|View full text |Cite
|
Sign up to set email alerts
|

Human Gait Recognition Using Deep Learning and Improved Ant Colony Optimization

Abstract: Human gait recognition (HGR) has received a lot of attention in the last decade as an alternative biometric technique. The main challenges in gait recognition are the change in in-person view angle and covariant factors. The major covariant factors are walking while carrying a bag and walking while wearing a coat. Deep learning is a new machine learning technique that is gaining popularity. Many techniques for HGR based on deep learning are presented in the literature. The requirement of an efficient framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…A study using three angles (0, 18 and 180) of the CASIA B dataset was presented in [9]. The data is normalized before being fed into two pre-trained models: ResNet101 and InceptionV3.…”
Section: Related Workmentioning
confidence: 99%
“…A study using three angles (0, 18 and 180) of the CASIA B dataset was presented in [9]. The data is normalized before being fed into two pre-trained models: ResNet101 and InceptionV3.…”
Section: Related Workmentioning
confidence: 99%
“…We review a few of them as shown in Figure 2 , namely [ 13 , 14 ], which worked on the identification of a person in crowded environments with low-resolution images as the source of input. Some other works are [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. However, Table 1 depicts the details of the environment constraints, the tools and techniques used, the methodology, the dataset and performance used by various researchers.…”
Section: Related Workmentioning
confidence: 99%
“…HAR has emerged as an impactful research area in CV from the last decade [ 22 ]. It is based on important applications such as visual surveillance [ 23 ], robotics, biometrics [ 24 , 25 ], and smart healthcare centers to name a few [ 26 , 27 ]. Several researchers of computer vision developed techniques using machine learning [ 28 ] for HAR.…”
Section: Related Workmentioning
confidence: 99%